Pengaruh Customer Satisfaction, Calculative Commitment, dan Corporate Image terhadap Attitudinal Loyalty dan Behavioral Loyalty Pada Program Pasti Prima Pertamina (Studi Pada SPBU Pasti Prima Wilayah Jakarta) - Rahma Sri Handayani; Citra Kusuma Dewi (Akademi Sekretari Manajemen Taruna Bakti, 2020)
This research is motivated by a previous observation result which show that customer satisfaction in using Pertamina's gas station services has been stagnant for the past several years. From these results, Pertamina created the latest gas station program namely